Clinical epidemiology of ALS in Liguria, Italy. Issue 1 (January 2013) - Bandettini di Poggio, Monica; Sormani, Maria Pia; Truffelli, Romina; Mandich, Paola; Origone, Paola; Verdiani, Simonetta; Mantero, Vittorio; Scialó, Carlo; Schenone, Angelo; Mancardi, Giovanni Luigi; Caponnetto, Claudia; ,
Abstract Our objective was to assess the incidence and trends of amyotrophic lateral sclerosis (ALS) in Liguria, a north-west region of Italy, utilizing a prospective design. Liguria (1, 615, 064 residents in 2010) is the site of a multicentre-multisource prospective population based registry called LIGALS (Liguria Amyotrophic Lateral Sclerosis Registry). All incident ALS cases during the period 2009–2010 were enrolled and followed up. Cases were identified using several concurrent sources. ALS diagnosis was based on the revised El Escorial criteria. One hundred and four cases were enrolled, generating an annual crude incidence of 3.22/100, 000 (95% CI 2.66−3.90), with a male/female ratio of 1.34. The annual standardized incidence, age and gender adjusted to the 2001 Italian population, was 2.51. At last observation on 1 March 2012, 45% of patients registered in the LIGALS had died, with a median survival of 45 months from symptoms onset. According to capture-recapture estimation, three patients were unobserved. For both genders, demographic and clinical features were collected. In conclusion, comparing these data to those of epidemiological studies with a similar prospective design, the occurrence of ALS is similar. The observed crude incidence was higher compared to other Italian studies, due in part to a very careful case ascertainment and in part to a high percentage of the elderly in Liguria.